Scottish Presbyterianism and the National Education Debates, 1850–62 - Mallon, Ryan (Studies in church history, 2019)
This article examines the mid-nineteenth-century Scottish education debates in the context of intra-Presbyterian relations in the aftermath of the 1843 ‘Disruption’ of the Church of Scotland. The debates of this period have been characterized as an attempt to wrest control of Scottish education from the Church of Scotland, with most opponents of the existing scheme critical of the established kirk's monopoly over the supervision of parish schools. However, the debate was not simply between those within and outside the religious establishment. Those advocating change, particularly within non-established Presbyterian denominations, were not unified in their proposals for a solution to Scotland's education problem. Disputes between Scotland's largest non-established churches, the Free Church and the United Presbyterian Church, and within the Free Church itself over the type of national education scheme that should replace the parish schools severely hampered their ability to express common opposition to the existing system. These divisions also placed increasing strain on the developing cooperation in Scottish Dissent on ecclesiastical, political and social matters after the Disruption. This article places the issue of education in this period within this distinctly Dissenting context of cooperation, and examines the extent of the impact these debates had on Dissenting Presbyterian relations.